2013
DOI: 10.1002/cncy.21288
|View full text |Cite
|
Sign up to set email alerts
|

Identification of EGFR mutation, KRAS mutation, and ALK gene rearrangement in cytological specimens of primary and metastatic lung adenocarcinoma

Abstract: BACKGROUND:The identification of molecular alterations has an important therapeutic implication in patients with lung adenocarcinomas. In the current study, the authors evaluated their experience with the identification of epidermal growth factor receptor (EGFR), Kirsten rat sarcoma viral oncogene homolog (KRAS) mutation, and anaplastic lymphoma kinase (ALK) gene rearrangement using cytological specimens of primary and metastatic lung adenocarcinoma. METHODS: A total of 54 cases of lung adenocarcinomas (11 pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 30 publications
1
47
1
Order By: Relevance
“…The frequency of EGFR mutation in the current study is comparable to those published from Korea, Japan, Italy and USA (25-29 %) [41,48,56,59] higher than those from Canada, France, Brazil and Japan (5-21 %) [38, 47, 51, 53], while lower in comparison to Taiwan, China and Mexico (33-54 %) [43,54,57]. In comparison to recent Indian studies, our frequency was pretty much similar to some studies 23-32 % [27, 65,66], though few studies even reported a much higher mutation rate varying between 39-52 % [28, 64,67] which could be attributed to small sample size, and or clinically selected patients.…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of EGFR mutation in the current study is comparable to those published from Korea, Japan, Italy and USA (25-29 %) [41,48,56,59] higher than those from Canada, France, Brazil and Japan (5-21 %) [38, 47, 51, 53], while lower in comparison to Taiwan, China and Mexico (33-54 %) [43,54,57]. In comparison to recent Indian studies, our frequency was pretty much similar to some studies 23-32 % [27, 65,66], though few studies even reported a much higher mutation rate varying between 39-52 % [28, 64,67] which could be attributed to small sample size, and or clinically selected patients.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, changes to the original slide due to molecular analyses (microdissection) can be avoided. Molecular analyses can even be repeated or complemented by other methods using the available serial sections [23]. Disadvantages of cell blocks compared to conventional cytology approaches refer to the sometimes reduced morphological quality (due to the spin down during processing), although others have even reported cell blocks to be helpful for a better demonstration of architectural patterns compared to ThinPrep specimens [24].…”
Section: Cell Blocks For Diagnostic and Predictive Analysesmentioning
confidence: 99%
“…Given the diversity of cytopathologic specimen types and the different methods of fixation and processing available, options for procuring DNA from cytologic specimens for molecular analysis vary; material can be successfully obtained from cell blocks, smears, cytospins, and liquid-based preparations. 7,9,11,12,14,[19][20][21][22][23][24][25] Most commonly, cell blocks are used for molecular testing on cytopathologic specimens. 21 The cell block closely approximates surgical pathology material; tissue fragments from cytopathologic specimens are embedded in paraffin and are sectioned akin to surgical specimens.…”
Section: Discussionmentioning
confidence: 99%